1975
DOI: 10.1042/bj1460001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phenobarbitone on protein synthesis by liver polyribosomes in fed and starved rats

Abstract: 1. The effect of phenobarbitone on the rate of protein synthesis and on the sedimentation patterns of various liver subcellular fractions containing ribosomes was studied in rats. 2. Phenobarbitone treatment increased the incorporation of [14C]leucine into protein by all preparations, provided they had not been subjected to preliminary treatment with Sephadex G-25. The phenobarbitone-induced effect on incorporation was associated with a gain in liver weight and a higher degree of polyribosomal aggregation. 3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 41 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that inducers may affect the initiation of protein synthesis and even translation central factors [94]. Phenobarbitone has been reported to increase C 14 -leucine incorporation into proteins by rat liver polyribosomes [95]. The increased RNA and protein synthesis as well as the stabilization and decreased degradation of these components has been implicated in the induction of drug metabolizing activity [96].…”
Section: Inducing Agents and Mechanism Of Inductionmentioning
confidence: 99%
“…It has been suggested that inducers may affect the initiation of protein synthesis and even translation central factors [94]. Phenobarbitone has been reported to increase C 14 -leucine incorporation into proteins by rat liver polyribosomes [95]. The increased RNA and protein synthesis as well as the stabilization and decreased degradation of these components has been implicated in the induction of drug metabolizing activity [96].…”
Section: Inducing Agents and Mechanism Of Inductionmentioning
confidence: 99%
“…Postmitochondrial supernatant was prepared as described by Blobel & Potter (1967). Incubation and determination of radioactivity incorporated into protein were performed as described by Ragnotti & Aletti (1975), with [3Hlleucine (0.5,uCi/sample).…”
Section: Amino Acid Incorporation By Postmitochondrial Supernatantmentioning
confidence: 99%